Analisis Sistem Dan Prosedur Pemberian Kredit Di Koperasi Simpan Pinjam Balo’ta Cabang Rinding Allo (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research is a qualitative research. This research discusses the analysis of the process and procedures for granting credit at the Balo'ta Savings and Loans Cooperative, Rinding Allo Branch. The purpose of this research is to determine the system and procedures for providing credit at the Balo'ta Savings and Loans Cooperative. The data collection procedures used were observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and conclusions. The result of this research is that the credit granting system at the Balo'ta Savings and Loans Cooperative, Rinding Allo Branch, minimizes financing problems using 5C, namely character, capacity, capital, collateral and condition of economy. However, there is still something lacking in the aspect of assessing customer character. The marketing team still does not follow the existing SOPs so there are quite a few errors in character assessment by customers. And the procedure for granting credit at the Balo'ta Savings and Loans Cooperative Rinding Allo Branch uses eight (8) methods, namely credit application, credit evaluation, credit negotiation, decision making, credit disbursement process, document archiving, collateral storage, and installment payment process. After a credit evaluation is carried out, it can be considered to be continued or rejected. The approval for taking credit will be signed by the head of the Rinding Allo branch at the Balo'ta Savings and Loans Cooperative.